"The Laryngectomee Guide" is available in 18 languages (Free eBooks). Issue 4 (1st October 2021) - Brook, Itzhak
Abstract : "The Laryngectomee Guide" contains information about the diagnosis and treatment of laryngeal cancer, side effects of radiation and chemotherapy; methods of speaking; airway, stoma, and voice prosthesis care; eating and swallowing; medical, dental and psychological concerns; respiration; anesthesia; and travelling. The Guide is available now in 18 languages (English, French, Italian, Portuguese, Spanish (4 versions), Bulgarian, Bosnian, Greece, Romanian, Turkish, Arabic, Persian, Simple and traditional Chinese, Korean, Japanese, Filipino, and Russian).